Doença pulmonar por micobacteria não tuberculosa (MNT): evolução clinica dos pacientes atendidos no HUJBB de janeiro de 2000 até dezembro de 2010. - NUNES, Lucas Lobato Acatauassu (2022)
Introduction – The description of the existence of non-tuberculous mycobacteria is considered done since the decade following the discovery of Mycobacterium tuberculosis in the nineteenth century. Initially, it was believed that these agents would not be capable of producing disease in humans. Now, after two centuries, their epidemiological importance is high-growth in Brazil, including the incorporation of these diseases in the list of compulsory notification of the Ministry of Health. Objective – To observe the clinical evolution of patients diagnosed with pulmonary disease caused by non-tuberculous mycobacteria treated at the University Hospital João de Barros Barreto. Methods – Analytical-descriptive study, retrospective, observational. The studied population was composed of patients treated for pulmonary disease caused by non-tuberculous mycobacteria who fulfilled the diagnostic criteria for this disease according to the American Thoracic Society. The period covered in the study is January 2000 to December 2010. The data were obtained from patients files, following a protocol pre-structured. Results – Nineteen patients were studied with isolation of nine species of non-tuberculous mycobacteria. The most used method for diagnosis was the smear with culture. There was great variety in treatment regimens used. Cure and evasion were the most frequent changes. Three patients were still undergoing treatment when the data were collected, so, it was not possible to observe the evolution in these cases. Conclusion – Lung infection by non-tuberculous mycobacteria is still a relatively recent topic. The lack of adequate supervision in the past was crucial to the high dropout rate found in this study. Today, the treatment currently carried out at Hospital João de Barros Barreto comes closer and closer to what is recommended by the Reference Center Hélio Fraga/FIOCRUZ and the American Thoracic Society.